TRANSFORMASI PARADIGMA TAFSIR AL-QUR’AN: ANALISIS EPISTEMOLOGIS DALAM TAFSIR MODERN DAN KONTEMPORER - Alya Zalfa Fitriady; Aimy Naziha R; Sarwan Hamid (Jurnal Akademika Kajian Ilmu-Ilmu Sosial, Humaniora Dan Agama, 2026)
Studies on Qur’anic exegesis continue to develop in line with changing perspectives on sources of knowledge, interpretive methods, and contextual frameworks. However, research examining this transformation from an epistemological perspective remains limited. This study aims to analyze the shift in the paradigm of Qur’anic exegesis from the classical period to the modern and contemporary eras, with a focus on changes in its underlying epistemological structure. This research employs a qualitative method based on library research using descriptive-analytical and comparative approaches. The findings indicate that the transformation of exegesis is not merely methodological but also epistemological, particularly in the relationship between revelation, reason, and context. Modern exegesis tends to integrate rationality with textual authority, while contemporary exegesis expands this framework through contextual and interdisciplinary approaches. The novelty of this study lies in its emphasis that the transformation of exegesis constitutes a dialectical process between normative tradition and historical dynamics. However, this expansion of interpretive space may also generate subjectivity; therefore, a balance between textual and contextual approaches is required to maintain the scientific validity of Qur’anic interpretation.